2010
DOI: 10.1177/0040517510373635
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the variability of vegetable fibres: a case study of harakeke (Phormium tenax)

Abstract: Fibre properties may be an important source of information to identify, conserve and protect intraspecific diversity within culturally significant fibre plants such as harakeke (Phormium tenax, New Zealand flax). M aori weavers recognise differences in wh ıtau * (fibre aggregate prepared using traditional practices) extracted from leaves of different harakeke cultivars. However, tensile properties of fibre aggregates are reportedly highly variable. The aim of this study was to investigate variation in fibre ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Acrylonitrile-butadiene-styrene (ABS) and polylactic acid (PLA) are available commercially and the most commonly used FDM materials, but there would be a benefit to improving the mechanical properties. However, polymer properties can be dramatically modified by the use of additives; blending with reinforcing fibres offers a range of advantages including reductions in shrinkage and increased mechanical properties [3][4][5][6] which could support the use of semi-crystalline polymers as desirable in FDM. The addition of short carbon fibre in ABS has been shown to increase tensile strength and Young's modulus, but decrease toughness, yield strength and ductility [7].…”
Section: Introductionmentioning
confidence: 99%
“…Acrylonitrile-butadiene-styrene (ABS) and polylactic acid (PLA) are available commercially and the most commonly used FDM materials, but there would be a benefit to improving the mechanical properties. However, polymer properties can be dramatically modified by the use of additives; blending with reinforcing fibres offers a range of advantages including reductions in shrinkage and increased mechanical properties [3][4][5][6] which could support the use of semi-crystalline polymers as desirable in FDM. The addition of short carbon fibre in ABS has been shown to increase tensile strength and Young's modulus, but decrease toughness, yield strength and ductility [7].…”
Section: Introductionmentioning
confidence: 99%
“…Many other processes are involved to make flax fibres usable for textile application such as scrapping, beating, washing, and dyeing (Pendergrast 1987). Variation in flax cultivars also causes variations in fibre properties, as investigated by Lowe et al (2010). Due to the property variation of different flax cultivars, Mäori (the indigenous people of New Zealand) weavers use different flax cultivars for different end-use applications: Tapamangu cultivar for baby shawls, and necklace ties; Arawa cultivar for excellent quality fibres; Takaiapu cultivar for medium quality fibres; and Takirikau cultivar for producing shiny fibres (Scheele and Walls 1994).…”
Section: Influence Of Different Cultivars Of Industrial Crops On Textmentioning
confidence: 99%
“…Due to the property variation of different flax cultivars, Mäori (the indigenous people of New Zealand) weavers use different flax cultivars for different end-use applications: Tapamangu cultivar for baby shawls, and necklace ties; Arawa cultivar for excellent quality fibres; Takaiapu cultivar for medium quality fibres; and Takirikau cultivar for producing shiny fibres (Scheele and Walls 1994). Lowe et al (2010) investigated tenacity of two different of cultivars (designated as B5 and F1) of New Zealand flax (Phormium tenax), which has been used by the Mäori for functional and cultural artifacts for a long time (Mead 1999;Scheele and Walls 1994) and found that the fibre tenacity was higher for B5 than F1. There was also a significant statistical difference between the tenacities of these two cultivars.…”
Section: Influence Of Different Cultivars Of Industrial Crops On Textmentioning
confidence: 99%
“…For example, tensile properties of muka vary considerably among cultivars when prepared with customary techniques and tested under identical test conditions (e.g. tenacity 0.3-0.7 N/tex; Lowe et al 2010). Nonaged muka from the 'Ngutunui' cultivar was found to have similar strength (N/tex) to that of non-aged Tapamangu and Makaweroa muka (tenacity: 0.50 vs. 0.53 and 0.55 N/tex, this study; (Carr et al 2005); two harakeke cultivars preferred for muka abstraction (Scheele 1997;Harris and Woodcock-Sharp 2000;Scheele 2005).…”
Section: Tensile Propertiesmentioning
confidence: 99%